I’m Not Dead Yet! The Role of the Operating System in a Kernel-Bypass Era - Zhang, Irene; Liu, Jing; Austin, Amanda; Stephenson, Justine; Badam, Anirudh (17th Workshop on Hot Topics in Operating Systems (HotOS), 2019)
Researchers have long predicted the demise of the operating system. As datacenter servers increasingly incorporate I/O devices that let applications bypass the OS kernel (e.g., RDMA and DPDK network devices or SPDK storage devices), this prediction may finally come true. While kernel-bypass devices do eliminate the OS kernel from the I/O path, they do not handle the kernel’s most important job:offering higher-level abstractions. This paper argues for a new high-level, device-agnostic I/O abstraction for kernel-bypass devices.We propose the Demikernel, a new library OS architecture for kernel-bypass devices. It defines a high-level, kernel-bypass I/O abstraction and provides user-space library OSes to implement that abstraction across a range of kernel-bypass devices. The Demikernel makes applications easier to build, portable across devices, and unmodified as devices continue to evolve.